2022
DOI: 10.1097/sap.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fat Grafting on Expansion Pressures in Expander-Based Postmastectomy Breast Reconstruction

Abstract: Introduction The impact of fat grafting on the viscoelasticity of irradiated tissues is poorly defined. We investigate the effect of subcutaneous fat grafting on postmastectomy tissue expansion in patients undergoing delayed breast reconstruction. We quantify observed viscoelastic and trophic changes of the skin envelope. We hypothesize that fat grafting changes the trophic and viscoelastic properties of the breast soft tissue envelope. Methods Postmast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Autologous fat grafting is commonly used for a variety of reconstructive and aesthetic surgery procedures in the face, buttocks, and breasts. [1][2][3][4][5] The American Society of Plastic Surgeons reported that more than 155,000 cosmetic procedures involving fat grafting were performed in 2020. 6 In a clinical setting, one of the major challenges of autologous fat grafting is poor graft retention, ranging from 25% to 90% overall volume loss over time.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous fat grafting is commonly used for a variety of reconstructive and aesthetic surgery procedures in the face, buttocks, and breasts. [1][2][3][4][5] The American Society of Plastic Surgeons reported that more than 155,000 cosmetic procedures involving fat grafting were performed in 2020. 6 In a clinical setting, one of the major challenges of autologous fat grafting is poor graft retention, ranging from 25% to 90% overall volume loss over time.…”
Section: Introductionmentioning
confidence: 99%